Pendampingan Sertifikasi Halal Self Declare bagi UMKM Pangan di Desa Pasanggar - Nasik, Khoirun; Ardyansyah, Farid; Hammam, Hammam (Santri : Journal of Student Engagement, 2025)
This service aims to improve the understanding and implementation of halal certification through a self declare scheme for Micro, Small, and Medium Enterprises (MSMEs) in the food and beverage sector in Pasanggar Village, Pegantenan District, Pamekasan Regency. The background of this activity is based on the mandate of the Job Creation Law Number 11 of 2020, which requires all business products to be halal certified. The implementation method includes initial surveys, focus group discussions, socialization regarding halal concepts and certification procedures, direct assistance in creating Business Identification Numbers, and the submission of halal certification through the SIHALAL platform. The results indicate that before the program was implemented, there were no SMEs in Pasanggar Village that had halal certification. After three months of intervention (September–November 2023), 18 SMEs successfully obtained halal certification. These findings demonstrate that an integrated approach through focus group discussions, socialization, and assistance is effective in accelerating the self-declaration-based halal certification process among SME actors